Health Personnel Practices Regarding Waste Management in the Delivery Room at the Middle Euphrates Teaching Hospitals - Zanab Neamat Jumaah; Muntahaa Abdullah Rashaan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Literatures proved that waste management is the most important and effective infection prevention andcontrol measure to prevent the spread of microorganisms causing HAIs is considering a vital intervention topromote optimum patient safety in delivery room. Aim of the study; This study conducted to assess wastemanagement practices of health care personnel in the delivery room at the middle Euphrates teachinghospitals. Methods; A Descriptive research design begin in 20th February to 26th May 2016, Current studysample involve all midwives and physicians in the delivery room (Total coverage.). Questionnaire usedfor data collection by interview forms and observational checklist was obtain from the extensive review ofrelevant literature and related studies Data analyzed through utilize (SPSS) software version (16) where,included descriptive analysis and inferential data analysis. The study conducted among 37 physicians and97 midwives working in the delivery room are females.Results: The current study indicate that good overall evaluation for the health staff practices concerningwaste management at Karbala while fair overall evaluation at Babylon, Diwaniah and Al-Najaf with highlysignificant in health staff practices regarding waste management and the different studied governoratesat p-value less than 0.01. Conclusion: based on the finding of present study majority of health carepersonnel have fair applies related to waste management practices at different studied governorate hospitals.Recommendations: Updating practice of health care personnel through continuing in-service educationalprograms. Regular inspection and follow-up from the ministry of health for assurances good wastemanagement, the important of exist motivation system and punishment system to the neglected health carepersonnel